Designing a Sustainable Value Proposition for MSMEs (Case Study: Watu Gunung Perkasa) - Definna Tarissa Syahmadina; Fajar Sidiq Adi Prabowo (Jurnal Wacana Ekonomi, 2025)
Currently, MSMEs have an important role in supporting the country’s economic growth. However, the challenge of creating a sustainable business amidst the increasing public awareness of environmental issues presents a unique challenge for MSME actors. This research aims to design a sustainable value proposition for Watu Gunung Perkasa, which operates in the natural stone processing sector. Additionally, the goal of this research is to maintain business relevance and enhance the competitiveness of  Watu Gunung Perkasa in the long term. This Study employs a qualitative exploratory method. Data collection in this research was conducted through in-depth interviews, observations, and documentation with the business owner and stakeholders. The results of the study indicate that Watu Gunung Perkasa has created value through the services and products it offers. However, there are still several opportunities that have not been fully utilized by Watu Gunung Perkasa. It can be seen that the value mapping tool is an effective analysis tool used to design sustainable value propositions for MSMEs with analysis of captured value, missed value, and value destruction. This research also can contribute to the development of the literature related to business sustainability in the context of MSMEs.